The Changes of Amino Terminal Pro B-type Natriuretic Peptide(NT-proBNP) Concentration and Left Ventricular EjectionFraction on Doxorubicin Chemotherapy Patients - Kamelia, Telly; Waspadji, Sarwono; Makmun, Lukman Hakim; Effendi, Shufrie; Ramli, Muchlis; Timan, Ina Susanti (UI Scholars Hub, 2017)
Introduction. Cancer patients who received chemotherapy regimen containing doxorubicin has been known to have serious side effect in heart, called as cardiotoxicity. The measurement of NT-proBNP proposed to be used as a new parameter to identify and evaluate cardiotoxicity in cancer patients earlier before it has been manifested, superior than measurement of left ventricle ejection fraction (LVEF). The aims of this study to examine the changes of NT-proBNP concentration and LVEF on patients with cancer who receive chemotherapy regimen containing doxorubicin. Methods. The study used pre and post test design to observe the changes of NT-proBNP concentration and LVEF on the patients who receive naïve doxorubicin chemotherapy and after chemotherapy-cycle I to cyce IV at the Ciptomangunkusumo hospital, Jakarta. Echocardiography and NT-proBNP were examined on naïve chemotherapy and after chemotherapy each cycle. Statistical analysis was performed by using two way Anova and Friedman nonparametric test. Results. During the period of October 2007 to June 2008, a total of 29 consecutive patiets receiving doxorubicin chemotherapy regimen CHOP (Cyclophosphamide, doxorubicin, Vincristine, Prednisone and FAC-5 Fluorouracil, doxorubicin, Cyclophosphamide) were collected. The increase of median NT-proBNP concentration between naïve chemotherapy and: post chemotherapy cycle I was 32 pg/mL (12,5-124,6 pg/mL), post chemotherapy cycle II was 135 pg/mL (44-275,2 pg/mL), post chemotherapy cycle III was 275,1 pg/mL (97,8-907,2 pg/mL), post chemotherapy cycle IV was 514,6 pg/mL (80,6-6458,2 pg/mL). With Friedman test, p< 0,000. With Anova two way test, it was found the difference between naïve LVEF and LVEF: post chemotherapy cycle I was 5,1% (p 0,000), post chemotherapy cycle II 8,9% (p 0,000), post chemotherapy cycle III 11,2% (p 0,000), post chemotherapy cycle IV 12,5% (p 0,000). Conclusions. Elevated NT-proBNP concentration and LVEF reduction had been observed in doxorubicin chemotherapy patients.